Outcome in Cardiac Electrophysiology and Radiofrequency Ablation of Atrioventricular Reciprocating Tachycardia - A Single Center Experience (Cardiovascular Journal, 2022)
Background: Radiofrequency catheter ablation is a curative modality of treatment for paroxysmal supraventricular tachycardia. The aim of our study was to evaluate our experience of electrophysiology procedures and radiofrequency ablation in atrioventricular reciprocating tachycardia (AVRT).Methods: All patients undergoing cardiac electrophysiology and radiofrequency ablation procedures during the period from July, 2019 to July, 2021 at Department of Cardiology, Evercare Hospital, Dhaka were included in this study. The study analyzed 141 patients of among them 75(53.2%) patients were male and 66(46.8%) were female.Results: Patients who came with AVRT, 91 (65%) had concealed and 50 (35%) had manifested. The overall short term success rate was 99 %. There was no difference in the success rates between the younger and older patients. Complication rate is lower side of the spectrum, which is 1.4% (four patients).Conclusion: Radiofrequency ablation is a safe and successful treatment modality for patients with atrioventricular reciprocating tachycardia in this real - world study.Cardiovasc j 2022; 15(1): 20-25